161k views
1 vote
If f(x)= -3x-5 and g(x)= 4x-2 find (f+g)(x)

2 Answers

2 votes

Answer:

Known :

f(x) = -3x - 5

g(x) = 4x - 2

Asked :

(f+g)(x) = ...?

Answer :

(f+g)(x) = (-3x - 5) + (4x - 2)

= (-3x + 4x) + (-5 - 2)

= x + (-7)

= x - 7

So, the value of (f+g)(x) is x - 7

Hope it helpful and useful :)

Explanation:

User DanielK
by
4.6k points
2 votes

Known :

f(x) = -3x - 5

g(x) = 4x - 2

Asked :

(f+g)(x) = ...?

Answer :

(f+g)(x) = (-3x - 5) + (4x - 2)

= (-3x + 4x) + (-5 - 2)

= x + (-7)

= x - 7

So, the value of (f+g)(x) is x - 7

Hope it helpful and useful :)

User Ruslan Osmanov
by
4.5k points